2009
DOI: 10.1007/s11655-009-0216-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tongxie Yaofang (痛泻要方) Granule in treating diarrhea-predominate irritable bowel syndrome

Abstract: TXYF is an effective preparation for the treatment of D-IBS. It can quickly lessen abdominal pain and distention, improve the property of stool, and improve mental tension and depression in patients. Its mechanism of action might be through the adjustment of MCs activation to decrease visceral hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 2 publications
0
41
0
Order By: Relevance
“…The variety in the prescriptions of TXYF caused significant heterogeneity in clinical effects. After the publication of the review, two trials with relatively sufficient power were conducted; and these two trials still used different TXYF prescriptions. One of the trials from Hong Kong conducted by Leung and colleagues used a prescription that consisted of 11 herbs and found negative results, the other trial by Pan and colleagues using the standard prescription that consisted of four herbs found positive results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variety in the prescriptions of TXYF caused significant heterogeneity in clinical effects. After the publication of the review, two trials with relatively sufficient power were conducted; and these two trials still used different TXYF prescriptions. One of the trials from Hong Kong conducted by Leung and colleagues used a prescription that consisted of 11 herbs and found negative results, the other trial by Pan and colleagues using the standard prescription that consisted of four herbs found positive results.…”
Section: Discussionmentioning
confidence: 99%
“…In Leung's study, they also demonstrated that: TXYF was not superior to placebo in adequate relief of IBS‐D global symptoms, but it was significantly better than placebo in relieving abdominal pain and daily stool frequency. In Pan's study, a self‐set measure assessing the improvement of overall IBS‐D symptoms was defined as the primary outcome . These facts indicate inconsistency in outcome measures in evaluating the effect of TXYF, and the definition of adequate relief of IBS‐D symptoms should be further developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that probiotics have favorable effects on IBS symptoms [29, 34, 35], whereas others did not prove the superiority of probiotics to placebo [36, 37]. In addition, some studies of Chinese herbal medicine also reported improvement of IBS-related symptoms or stool form in the study group [38, 39], whereas others found no significant differences between the study and placebo groups [28, 40]. Recent studies assessing the effects of DUO or herbal medicine on quality of life reported no statistical differences between the study and placebo groups [11, 28].…”
Section: Discussionmentioning
confidence: 99%
“…A series of randomized, double-blind, placebo-controlled trials had shown that TongXie-YaoFang (TXYF) formula can significantly improve the clinical symptoms, such as diarrhea and abdominal pain or discomfort, of patients with D-IBS and improve the quality of their lives[9,10]. However, the specific mechanism of it has not been completely elaborated.…”
Section: Introductionmentioning
confidence: 99%